Cognitive benefits of folic acid supplementation during pregnancy track with epigenetic changes at an imprint regulator - L. Hilman; M. Ondičová; A. Caffrey; M. Clements; C. Conway; M. Ward; K. Pentieva; R. E. Irwin; H. McNulty; C. P. Walsh (BMC Medicine)
Abstract Background The human ZFP57 gene is a major regulator of imprinted genes, maintaining DNA methylation marks that distinguish parent-of-origin-specific alleles. DNA methylation of the gene itself has shown sensitivity to environmental stimuli, particularly folate status. However, the role of DNA methylation in ZFP57’s own regulation has not been fully investigated. Methods We used samples and data from our previously described randomised controlled trial (RCT) in pregnancy called Folic Acid Supplementation in the Second and Third Trimester (FASSTT), including follow-up of the children at age 11. Biometric and blood biochemistry results were examined for mothers and children. Methylation of ZFP57 was analysed by EPIC arrays, pyrosequencing and clonal analysis, and transcription assessed by PCR-based methods. Functional consequences of altered methylation were examined in cultured cells with mutations or by inhibition of the main DNA methyltransferases. DNA variants were examined using pyrosequencing and Sanger sequencing, with results compared to published studies using bioinformatic approaches. Cognitive outcomes were assessed using the Wechsler Intelligence Scale for Children 4th UK Edition (WISC-IV), with neural activity during language tasks quantified using magnetoencephalography (MEG). Results Here we show that methylation at an alternative upstream promoter of ZFP57 is controlled in part by a quantitative trait locus (QTL). By altering DNA methylation levels, we demonstrate that this in turn controls the expression of the ZFP57 isoforms. Methylation at this region is also sensitive to folate levels, as we have previously shown in this cohort. Fully methylated alleles were associated with poorer performance in the Symbol Search and Cancellation subtests of WISC-IV in the children at age 11 years. There were also differences in neural activity during language tasks, as measured by MEG. Analysis of published genome-wide studies indicated other SNPs in linkage disequilibrium with the mQTL were also associated with neurodevelopmental outcomes. Conclusions While numbers in the current RCT were small and require further validation in larger cohorts, the results nevertheless suggest a molecular mechanism by which maternal folic acid supplementation during pregnancy may help to counteract the effects of folate depletion and positively influence cognitive development in the offspring.